EFEKTIVITAS MODEL PEMBELAJARAN TWO STAY TWO STRAY DENGAN CONCEPT MAP DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI SISWA DI SMAN 1 BARRU - Usman Usman; Nurleli Ramli; Hasmiah Herawaty; Wirawan Setia Laksana (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
This research aims to reveal the ability of interpersonal communication among students after the implemention of the learning model of concept map, two stay two stray, and two stay two stray with concept map. This research was experiment type designing the factorial pre test – post test involving two variables – two stay two stray and concept map. The object of this research was two senior high schools at Barru, South Sulawesi. The respondents in this research were 122 students. The result disclosed that the instrument of the ability of interpersonal communication among students has valid and reliable of Cronbach Alpha 0.822. The change of communication as independent variable revealed that the learning model of concept map, two stay two stray, and two stay two stray with concept map provides positive effects on the ability of interpersonal communication among students. The learning model of two stay two stray provided the greatest effect with the value of 32.4%. The effect of concept map using the same size only provided the value of 7.8% and the combination of both only provided the value of 4.4%. The further result revealed that the response of teachers on the the given treatment has positive and students have positive response and assess that the given treatment supports their learning in the classroom.